Pengaruh Digital Marketing dan E-Commerce terhadap Customer Loyality pada Barokah Shop Gorontalo - Putri Ayu Hula; Meimoon Ibrahim; Elfis Mus Abdul (Jurnal Simki Economic, 2025)
This research aims to assess the impact of digital marketing and e-commerce on customer loyalty at Barokah Shop Gorontalo. The study applies a quantitative approach with data collected through questionnaires distributed to ninety-nine respondents who are customers of Barokah Shop Gorontalo. The data were analyzed using multiple linear regression to determine the effect of each variable on customer loyalty. The results show that both digital marketing and e-commerce, whether assessed individually or together, have a positive and significant influence on customer loyalty. These findings indicate that the implementation of effective digital marketing strategies and the optimization of e-commerce practices can substantially enhance customer loyalty. The outcomes of this research suggest the importance of integrating digital marketing and e-commerce into business strategies to sustain and improve customer engagement at Barokah Shop Gorontalo.